Hubungan Antara Sikap Terhadap Sistem Zonasi PPDB fan Motivasi Berprestasi Siswa SMPN 2 Wagir - Arum Sekar Purwono Putri; Fattah Hanurawan (Flourishing Journal, 2021)
Abstract: The objectives of this study include: (1) to describe the attitudes of SMP 2 Wagir students towards the PPDB zoning system (2) to determine the description of the achievement motivation of SMPN 2 Wagir students regarding the implementation of the PPDB zoning system (3) to determine the relationship between attitudes towards the PPDB zoning system and achievement motivation in students of SMP 2 Wagir. This research uses a quantitative approach with descriptive correlational research. The population of this research is 546 students. The sampling technique used was random sampling so that the research subjects were 82 students at SMPN 2 Wagir. Subject data retrieval is done through the distribution of google forms. The instrument used was a scale of attitudes and a scale of achievement motivation with reliability of 0.849 and 0.910, respectively. The results showed that (a) students of SMPN 2 Wagir have a positive attitude towards the PPDB zoning system by 67 percent (b) SMP 2 Wagir students have high achievement motivation by 73 percent (c) there is a relationship between attitudes towards the PPDB zoning system and achievement motivation students of SMP 2 Wagir. The value obtained from the hypothesis test analysis is 0.644 with a significant level of 0.000. Keywords: Attitudes towards the zoning system, achievement motivation, students of SMP 2 Wagir Abstrak: Tujuan dari penelitian ini meliputi: (1) untuk mengetahui gambaran sikap siswa SMPN 2 Wagir terhadap sistem zonasi PPDB (2) untuk mengetahui gambaran motivasi berprestasi siswa SMPN 2 Wagir terkait penerapan sistem zonasi PPDB (3) untuk mengetahui hubungan antara sikap terhadap sistem zonasi PPDB dan motivasi berprestasi pada siswa SMPN 2 Wagir. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian deskriptif korelasional. Populasi penelitian ini berjumlah 546 siswa. Teknik sampling yang digunakan yaitu random sampling sehingga didapatkan subjek penelitian sebanyak 82 siswa di SMPN 2 Wagir. Pengambilan data subjek dilakukan melalui penyebaran google form. Instrumen yang digunakan berupa skala sikap dan skala motivasi berprestasi dengan masing-masing reliabilitas 0,849 serta 0,910. Hasil penelitian menunjukkan bahwa (a) siswa SMPN 2 Wagir secara memiliki sikap terhadap sistem zonasi PPDB positif sebesar 67 persen (b) siswa SMPN 2 Wagir memiliki motivasi berprestasi tinggi sebesar 73 persen (c) terdapat hubungan antara sikap terhadap sistem zonasi PPDB dan motivasi berprestasi siswa SMPN 2 Wagir. Nilai yang didapatkan dari analisis uji hipotesis sebesar 0,644 dengan taraf signifikan sebesar 0,000. Kata kunci: Sikap terhadap sistem zonasi, motivasi berprestasi, siswa SMPN 2 Wagir